(untitled) (The Research of Medical Science Review, 2025)
Background: In December 2019, an epidemic viral disease spread which later converted into a pandemic viral disease, this viral infection is known as COVID-Severe Acute Respiratory Syndrome Coronavirus 2 is the pathogenic and highly transmissible virus that causes COVID-19 disease. Pakistan is one of the major countries affected by SARS-CoV-2 with fatal consequences. Objective: The purpose of this investigation was to investigate the expression of interleukin-10 in healthy, severe to critical, and COVID-19 mild to moderate sufferers by ELISA and RT-PCR. Methods: The study was conducted among 150 adult patients with COVID‐19 (Classification as mild/moderate and severe patients. Serum samples were tested for IL-10 levels and expression by ELISA and Real-time PCR. The statistical analysis was performed using Graph Pad prism software and the Kruskil Walis test was applied. Results: The median levels of IL-10 in healthy, mild/moderate, and severe patients are 6.45, 6.78, and 7.44. While the p-value is insignificant (p 0.269). The expression of IL-10 was studied in the peripheral blood of patients with severe COVID-19 compared to mild/moderate symptomatic COVID-19 and healthy individuals. In the peripheral blood of COVID-19 patients, the level of IL-10 mRNA was 6.024 in severe cases and 4.58 in mild to moderate subjects (1). Notable differences were noted in the expression of interleukin-10 in the circulating cells of sever COVID-19 patients compared to those with mild cases and the control group. Conclusion: In conclusion, IL-10 levels and expression are higher in severe and mild/moderate patients as compared to healthy individuals which may contribute to the pathogenicity of COVID-19 patients.